1645g The experience of work. (24th April 2018) - Nicholas, R
Abstract : Introduction: In its most ideal state, work can provide an opportunity for us to experience and explore ourselves through our work. We can experience ourselves through our identity, our understanding as a whole person, our core values, our internal motivations, and our behaviours that arise from our core values and motivations. Methods: One way to explore all this is through the practice of inquiry—simply by asking, who are we when we work? The answer is not some kind of intellectual exercise where we analyse or quantify ourselves. Instead, the answer comes from how we experience ourselves, our coworkers, and the work itself. Results: In the right work environment, we have the opportunity to experience ourselves in ways that are unique for each of us. We can come to understand ourselves through our work—through our awareness, our relationships, our self-excellence, and how we bring our whole selves, our human spirit, to our work. When work nourishes the human spirit, we can live the greater parts of ourselves. This is the potential experience of the whole person, because indeed, each person is greater than the sum of their parts. Discussion: Because of who we are at work, we can dedicate ourselves to our families, we can learn and grow, we can create, and we can contribute to something bigger than ourselves. The ultimate gift of work is that experiencing ourselves at work can lead to experiencing ourselves in life. The reverse is equally true, because who we are in life is who we are at work. Keats wrote, 'Nothing ever becomes real till it is experienced.' Work has the potential to provide that real experience.